Ethical considerations for older adults - Dev, Priya S.; Eljo, J.O. Jeryda Gnanajane (Nusantara Journal of Behavioral and Social Science, 2024)
This article conjointly presents an outline of ethical considerations among older adults by addressing policy choices, quick and future prospects to adapt to population aging, and provides the list of schemes and programs that support to older adults and their families. It concludes with the necessity to require care for the older population which will be very helpful for future research in this area. It also helps to know the timely action required from the part of government, nonpublic corporations, researchers and also the general population. The objectives of this paper are to review ethical considerations among older adults through detailing elderly care and ethical issues on health care services for the elderly and to examine the adequacy of the existing health care services and policies provided to the elderly people. A review of relevant literature was performed to elaborate the ethical considerations among older population. A total of 16 qualified published literature's of all years until 2019 were collected from several electronic database and manual search are included in this review. According to the law and medical ethics in older people, there were several considerations that need to carried out in the service of the elderly care, those are ethical principles and emotional difficulties associated with living with chronic conditions. The requirement to extend older adults’ access to psychological state support is well acknowledged in recent reports, notably within the case of older adults with chronic conditions.  In the practice of geriatric services in our country, several aspects should be a considerations by following the law and policies.